Enabling agroecological transitions in Ethiopia: The role of incentives, business models and partnerships. Insights from the PSii kick-off workshop - Balcha, Yodit; Tibebe, Degefie; Mockshell, Jonathan; Ogutu, Sylvester; Blum, Helen (2023)
As Africa's second-largest wheat producing country, wheat production is an important source of income and food security for farmers in Ethiopia. Nevertheless, the country heavily relies on imports for more than half of its wheat consumption. However, the effort to produce wheat mainly follows an industrial agriculture approach which is characterized by intensive external input uses. Consequently, it might not be sustainable as it has an impact on the environment and natural resources. Furthermore, climate change is expected to worsen the situation of wheat production unless agroecological practices are implemented. To address this, the TRANSITIONS- PSii project aims to implement agroecological practices as solutions to enhance sustainable wheat production, maintain the environment, and reduce dependency on imports.